Expatriates motivation, adjustment and repatriation : reasons why Icelandic citizens expatriate to Norway and why they repatriate to Iceland from Norway. - Sandra Rún Jóhannesdóttir 1985- (2013)
Businesses and organizations are increasingly becoming international in scope. It is more and more common that individuals as well as organizations view business skill development and foreign work experience as an increasingly important part of career progression. That applies to Icelandic individuals as well. The Nordic countries have been a very popular destination for Icelandic citizens and especially Norway after the economic collapse in October 2008. As it has been reported in the press, everything is apparently better outside of Iceland and it is especially better to live in Norway. The press has been reporting the expatriation of Icelandic citizens but their reports have been fairly homogenous. This thesis examines the essential motivating factors of Icelandic citizens who are self-initiated expatriates and the reasons why they choose to expatriate to Norway. It also explores how well the Icelandic expatriates are adjusting to the life in Norway regarding general, work and interaction adjustment. Lastly this research examines what factors push, pull and/or shock Icelandic expatriates to repatriate back to Iceland from Norway. The research consists of qualitative interviews with five Icelandic self-initiated expatriates and five Icelandic repatriates. The main conclusions show that the Icelandic citizens moving to Norway is more diverse than the press has been reporting and that the reasons for expatriating are more than just because of unemployment and financial difficulties. The research also shows that the need to be close to the immediate and extended family has an effect on how long Icelandic citizens live in Norway. Keywords: Self-initiated expatriates, Organizational expatriates, motivation, adjustment, repatriation, Icelandic citizens